2009
DOI: 10.1007/s11605-009-0872-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Gastrointestinal Stromal Tumors of the Stomach

Abstract: Histologically proven complete resection is an effective treatment for gastric GIST. Laparoscopic procedures were carried out successfully in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 33 publications
2
41
0
3
Order By: Relevance
“…In this report, we analyzed the results of a homogenous population of 151 patients with primary GIST treated by the GISTologist Study Groupduringthepast11years.Thedisease-freesurvivalrate forall151patientsinthisstudywas77%at5years,whichis similar to the results of Silberhumer et al [5] who reported 85%survivalat5yearsinagroupof63patients.…”
Section: Discussionsupporting
confidence: 89%
“…In this report, we analyzed the results of a homogenous population of 151 patients with primary GIST treated by the GISTologist Study Groupduringthepast11years.Thedisease-freesurvivalrate forall151patientsinthisstudywas77%at5years,whichis similar to the results of Silberhumer et al [5] who reported 85%survivalat5yearsinagroupof63patients.…”
Section: Discussionsupporting
confidence: 89%
“…3 Although the majority of SETs are considered benign, some do have malignant potential. 4,5 In the present study, the prevalence of gastric SETs was 1.7%, and that increased with age. In Korea, the national healthcare program recommends gastroscopy every two years irrespective of the presence of symptoms.…”
Section: Discussionsupporting
confidence: 48%
“…However, there are limited data comparing traditional open versus laparoscopic resection of these tumors [13][14][15][16][17][18][19]. The aim of the current study was to assess the feasibility and safety of minimally invasive surgery for treating gastric stromal tumors and to compare laparoscopic to open surgery in the management of these neoplasms.…”
mentioning
confidence: 99%